(untitled) (Research, Society and Development, 2025)
Introduction: Understanding speech is more difficult in noisy environments and tends to degrade even further with aging. Hearing in noise is a complex process that requires multiple systems, including cognition, which can be assessed through the P300 auditory potential. It is widely believed that speech perception worsens in noise, but this performance varies between individuals, even with similar pure-tone audiograms. Objective: To analyze whether P300 latency and amplitude differ significantly between older and younger adults in quiet and noise. Method: This systematic review searched for observational studies comparing the differences in P300 latency and amplitude results between older and younger adults in quiet and noise, without language or date restrictions, in the following databases: MEDLINE, ScienceDirect, Scopus, Web of Science, SciELO, Cochrane Central, Embase, LILACS, and Circumpolar Health Bibliographic. Results: The search on the databases found 21,727 results, of which 302 titles were selected. Of these, 61 were excluded due to repeated titles, leaving 241 abstracts to be read. Then, 40 full texts were selected. Next, 37 articles were excluded for not meeting the eligibility criteria, leaving 3 articles eligible. Conclusion: The elderly presented a prolonged mean P300 latency in silence compared to the young. In the presence of noise, the mean P300 latency was prolonged in both groups.